An Introduction to Mathematics for Students of Economics - Lewis, J. Parry (London: Macmillan, New York: St. Martins Press, 1966)
This is not a book about economics; nor is it written for anybody but the student of economics. It is essentially what its title claims, and attempts to provide the student who has done little, if any, mathematics with an introduction which starts at a very simple level but goes quite a long way. The book is divided into sections. The First revises elementary algebra, starting from the very beginning, and then leading to more complicated ideas. The second introduces some trigonometry and co-ordinate geometry, once again without assuming any previous knowledge of these subjects. The third section is concerned with the calculus, and is illustrated by references to a number of economic problems. In the next section these ideas are extended to cases where many variables are involved. The fifth section develops certain ideas which are of use in cycle theory.
Includes bibliography and index.
ne 23/03/2018
Loans
Keywords: Business Mathematics